Evaluation of hydro-alcoholic extract of Eclipta alba for its anticancer potential: An in vitro study - Chaudhary, Harshita; Dhuna, Vikram; Singh, Jatinder; Kamboj, Sukhdev Singh; Seshadri, Sriram (Journal of ethnopharmacology, 2011)
Eclipta alba is traditionally used as hepatoprotective agent. The study was designed to explore its antiproliferative activity on liver and other related cancer. The present study was designed to assess and establish the role of Eclipta alba as anti-cancer agent using HepG2, C6 glioma and A498 cell lines as model system. Antiproliferative and cytotoxic effects of the Eclipta alba hydroalcoholic extract (EAE) was determined using MTT assay. The expression level of NF-kB was analysed by western blotting and RT PCR. Gelatin zymography was done for gelatinase matrix metalloproteinases (MMP-2 and 9) analysis. EAE inhibited the cell proliferation in dose dependent manner in HepG2, A498 and C6 glioma cell lines with an IC50 of 22±2.9, 25±3.6 and 50±8.7μg/ml, respectively. The expression of MMP (2 and 9) was down-regulated with EAE treatment. DNA damage was observed following 72h of extract treatment, leading to apoptosis. Additionally, the expression level of NF-kB was evaluated with western blotting and RT-PCR and was found to be down-regulated/inactivated. The data establish the existence of anti-proliferative, DNA damaging and anti-metastasis properties in EAE which is yet unexplored and hold high therapeutic impact.